PENGARUH PENGENDALIAN INTERNAL, KOMPENSASI DAN PERSONAL ATTITUDE TERHADAP FRAUD PADA PT REVIMA FITNESS INDONESIA - Mega Andani; Indra Saputra; Iin Parlina (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This research aims to examine and analyze the effect of Internal Control, Compensation and Personal Attitude on Fraud at PT Revima Fitness Indonesia. The population of this research are all employees of PT Revima Fitness Indonesia. The research sample used saturated sampling of 36 people. Analysis using logistic regression. The results of the research show that Internal Control has an effect on Fraud at PT Revima Fitness Indonesia. Compensation has an effect on PT Revima Fitness Indonesia's fraud. Personal attitude influences PT Revima Fitness Indonesia's fraud. Internal Control, Compensation, Personal attitude towards PT Revima Fitness Indonesia fraud.